Racial/ethnic and gender disparity in the severity of NAFLD among people with diabetes or prediabetes - Shaheen, Magda; Schrode, Katrina M.; Tedlos, Marielle; Pan, Deyu; Najjar, Sonia M.; Friedman, Theodore C. (Frontiers in Physiology, 2023)
Aim: Non-alcoholic fatty liver disease (NAFLD) exhibits a racial disparity. We examined the prevalence and the association between race, gender, and NAFLD in populations with prediabetes and diabetes among prediabetes and diabetes populations in adult US population. Methods: We analyzed data for 3,190 individuals >18 years old from the National Health and Nutrition Examination Survey (NHANES) 2017-2018. NAFLD was diagnosed by FibroScan® using controlled attenuation parameter (CAP) values: S0 (none) <238, S1 (mild)=238-259, S2 (moderate)=260-290, S3 (severe) >290. Data were analyzed using Chi-square test and multinomial logistic regression, adjusting for confounding variables and considering the design and sample weights. Results: Of the 3,190 subjects, the prevalence of NAFLD was 82.6%, 56.4% and 30.5% (p<0.0001) among diabetes, prediabetes and normoglycemia populations respectively. Mexican American males with prediabetes or diabetes had the highest prevalence of severe NAFLD relative to other racial/ethnic groups (p<0.05). In the adjusted model, among the total, prediabetes, and diabetes populations, a one unit increase in HbA1c was associated with higher odds of severe NAFLD (adjusted odds ratio [AOR]=1.8, 95% confidence level [CI]=1.4-2.3, p<0.0001; AOR=2.2, 95% CI=1.1-4.4, p=0.033; and AOR=1.5, 95% CI=1.1-1.9, p=0.003 respectively). Conclusion: We found that prediabetes and diabetes populations had a high prevalence and higher odds of NAFLD relative to the normoglycemic population and HbA1c is an independent predictor of NAFLD severity in prediabetes and diabetes populations. Healthcare providers should screen prediabetes and diabetes populations for early detection of NAFLD and initiate treatments including lifestyle modification to prevent the progression to non-alcoholic steatohepatitis or liver cancer.